Explaining the Vitality of Eighteenth-century Non-Muslim Ottoman Merchants: How to Cope with Transaction Costs. (November 2019) - Kadı, İsmail Hakkı
The role of non-Muslim communities in the Ottoman Empire has been a topic of debate among scholars who approached the issue from various perspectives at different times. One thread in this debate focused on these communities' role in Ottoman trade with Europe and emphasized their relations with western capital in explanation of their prominence in the Ottoman economy. This article attempts to explain the vitality of non-Muslim merchants through the centuries in the face of Western economic penetration of the Ottoman Empire, by focusing on transaction costs and market imperfections in North-western Anatolia. The article focuses on the trade in mohair yarn and cotton, which were the most important commodities exported to the Netherlands from the Ottoman Empire. Relying on data obtained from Dutch archives on cotton and mohair yarn consignments from Ankara and Izmir to Amsterdam, the article emphasises the diversity and complexity of the various transactions and expenses required to deliver these consignments to Amsterdam. It suggests that the local merchants were able to take advantage of the market imperfections and high transaction costs in North Western Anatolia while interacting with European merchants in the region.